Knowledge and conduct of pharmacists for dispensing of drugs in community pharmacies: a cross-sectional study - Reis, Tiago Marques dos (2015)
The objective of the study was to evaluate the knowledge of pharmacists and check their conduct in relation to dispensing of drugs. This is a cross-sectional study performed in four municipalities from South and Southeast of Brazil, which are reference in health national scenario and concentrate 73.6% of national economic activity. Pharmacists who works in community pharmacies were invited to answer a questionnaire prepared by the authors of this study and validated. The main outcome measured was the pharmaceutical knowledge, rated according to the number of correct answers on that questionnaire prepared by the researchers, and professional conduct in relation to dispensing of drugs. The data collection occurred from September to December 2012 and the information obtained were tabulated in duplicate by two independent researchers for later analysis. 486 community pharmacies were visited but only 112 professionals participated in the study. Among the participants, 78.6% (n = 88) did not have adequate knowledge to perform the dispensing of drugs, despite this same number of pharmacists claiming to have participated in conferences and courses after graduation. The main sources of information on drugs used by participants have a low level of scientific evidence. The performance of non-employment related tasks reduces the time available for the care of medication users. In addition, the indiscriminate sale of antimicrobials and the sale of products other than health, mischaracterize the role of the pharmacist in the community pharmacy. There are gaps in the knowledge of professionals, limiting the satisfactory completion of dispensing of drugs. In addition, the excess of other duties and inadequate professional conduct compromise the promotion of the rational use of drugs.